2021
DOI: 10.1007/s10735-020-09936-y
|View full text |Cite
|
Sign up to set email alerts
|

Uremic toxin indoxyl sulfate promotes proinflammatory macrophage activation by regulation of β-catenin and YAP pathways

Abstract: Evidence has been shown that indoxyl sulfate (IS) could impair kidney and cardiac functions. Moreover, macrophage polarization played important roles in chronic kidney disease and cardiovascular disease. IS acts as a nephron-vascular toxin, whereas its effect on macrophage polarization during inflammation is still not fully elucidated. In this study, we aimed to investigate the effect of IS on macrophage polarization during lipopolysaccharide (LPS) challenge. THP-1 monocytes were incubated with phorbol 12-myri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Consistent with previous experimental [11,24] and clinical [12,25] findings, our study demonstrated a direct correlation between serum IS levels and the concentrations of proinflammatory markers, such as CRP, IL-6, MCP-1, and TNF-α. These findings provide further evidence of the proinflammatory effects of IS in patients undergoing HD.…”
Section: Abbreviation: Bmi -Body Mass Index Crp -C-reactive Protein H...supporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous experimental [11,24] and clinical [12,25] findings, our study demonstrated a direct correlation between serum IS levels and the concentrations of proinflammatory markers, such as CRP, IL-6, MCP-1, and TNF-α. These findings provide further evidence of the proinflammatory effects of IS in patients undergoing HD.…”
Section: Abbreviation: Bmi -Body Mass Index Crp -C-reactive Protein H...supporting
confidence: 92%
“…Indoxyl sulfate (IS), a uremic toxin generated by gut microbiota from dietary tryptophan, has emerged as a potential key mediator of chronic inflammation in CKD [10]. It has been shown to activate inflammatory pathways and promote oxidative stress, contributing to the systemic inflammation observed in patients treated with maintenance HD [10][11][12][13]. Elevated levels of IS have been associated with various adverse outcomes in CKD, including cardiovascular disease and mortality [14,15].…”
mentioning
confidence: 99%
“…In this study, as M2 macrophages were rarely observed in the UCM heart (data not shown), the majority of macrophages were thought to be M1 macrophages. This finding suggested that M1 macrophages might be polarized by a uraemic toxin 27 and the activation of PlGF/Flt‐1 signalling, and the sustained pro‐inflammatory environment lead to the development of interstitial fibrosis, 14,16,25,26 which is consistent with the degree of interstitial fibrosis to be higher with a longer duration of RRT.…”
Section: Discussionmentioning
confidence: 69%
“…IS can activate and upregulate several meditators involved in itching such as protease-activated receptor-2, [38][39][40] cannabinoid receptor type 1, 41,42 NLRP3 Inflammasome, 43,44 endothelin-1, 45,46 signal transducer and activator of transcription 3, 47,48 astrocyte activity, 49,50 NADPH oxidase, 51,52 transient receptor potential vanilloid 1, 53,54 Intercellular Adhesion Molecule 1 (ICAM-1), 55,56 Transforming growth factor-β (TGF-β), 57,58 and macrophage. 59,60 In addition, IS can downregulate antiitching mediators such as nuclear factor E2-related factor 2. 61,62 Also, IS is a neurotoxin and can initiate neuroinflammation and induce cognitive impairment and behavioral abnormality, [63][64][65][66][67] which can exacerbate itching.…”
Section: Discussionmentioning
confidence: 99%